The Effects of Online Learning on Psychomotor Changes in Short Story Writing for Students of Class VII of SMPN 4 Banda Aceh - Erfinawati, Erfinawati; Ismawirna, Ismawirna; Yulsafli, Yulsafli; Darmawati, Darmawati (Universitas Serambi Mekkah, 2021)
The purpose of this study was to describe the effects of online learning on psychomotor changes in short story writing among students of SMPN 4, Banda Aceh. The data were taken from the students’ short stories at SMPN 4 Banda Aceh. The methods used were descriptive qualitative and quantitative. Techniques used to collect the datawerea test, observation, interview and documentation. The data were then processed using the SPSS program. Based on the results of the linearity test, there was a significant linear relationship between psychomotor changes (X) and learning in short story writing (Y). However, this relationship was only slightly affected, namely 8.6% while the rest was influenced by external factors from the research variables, namely laziness and student boredom. The results of the regression test also show that online learning at SMPN 4 Banda Aceh has no significant effects on psychomotor changes in writing short stories. Meanwhile, the results of interviews with teachers and students revealed that online learning has positive and negative effects depending on the learning patterns. Keywords: online learning, psychomotor, short stories writing.